2016
DOI: 10.1039/c5nr08101g
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive terahertz modulation by silicon-grown MoS2nanosheets

Abstract: Two-dimensional (2D) materials play more and more important roles these days, due to their broad applications in many areas. Herein, we propose an optically-pumped terahertz (THz) modulator, based on Si-grown MoS2 nanosheets. The broadband modulation effect has been proved by THz time domain spectroscopy and numerical simulation. The modulation depth of this Si-grown MoS2 nanosheet can reach over 75% under the low pumping power of 0.24 W cm(-2), much deeper than that of bare silicon. By theoretical models and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(68 citation statements)
references
References 35 publications
1
67
0
Order By: Relevance
“…16 Recently, we have found that a catalytic effect on THz modulation in the Si-grown MoS 2 , which can significantly enhance the modulation depth compared with bare Si wafer under the same weak CW laser pumping. 17 The unique band structure of MoS 2 -Si heterostructure and the high mobility of MoS 2 make more carriers are generated on the Si surface. Shortly afterwards, a similar experiment result has also been confirmed by Cao et al, 18 and they have explained the enhancement mechanism in more details.…”
mentioning
confidence: 99%
“…16 Recently, we have found that a catalytic effect on THz modulation in the Si-grown MoS 2 , which can significantly enhance the modulation depth compared with bare Si wafer under the same weak CW laser pumping. 17 The unique band structure of MoS 2 -Si heterostructure and the high mobility of MoS 2 make more carriers are generated on the Si surface. Shortly afterwards, a similar experiment result has also been confirmed by Cao et al, 18 and they have explained the enhancement mechanism in more details.…”
mentioning
confidence: 99%
“…As Shown in Figure 3b,c, with the bias current changing from 0 to 1800 mA, the transmission generally decreases from 0.60 to 0.003 in the range of 0.2-1 THz. [41][42][43][44][45][46][47][48][49][50][51] For the BST-silicon sample, we attribute the broadband modulation to the interaction between the carrier layer and THz waves. The threshold current changes from 1000 to 900 mA.…”
Section: Preparation and Characterization Of Thz Modulatorsmentioning
confidence: 99%
“…Accordingly, for sufficient high fluences and frequencies lower than the scattering rate Îł, the semiconductor can exhibit a "metallic" behaviour and a negative dielectric constant. Interestingly, even complex 2D materials such as graphene or MoS 2 , whose bandgap depends on the number of layers [19,20], can be described by the Drude model at THz frequencies in the first approximation. Graphene is a bidimensional material which derives much of its remarkable properties from its zero bandgap and conical energy dispersion.…”
Section: Basic Theoretical Principlementioning
confidence: 99%